2020
DOI: 10.1016/j.stem.2020.03.005
|View full text |Cite
|
Sign up to set email alerts
|

GATA3 Mediates a Fast, Irreversible Commitment to BMP4-Driven Differentiation in Human Embryonic Stem Cells

Abstract: Summary During early development, extrinsic triggers prompt pluripotent cells to begin the process of differentiation. When and how human embryonic stem cells (hESCs) irreversibly commit to differentiation is a fundamental yet unanswered question. By combining single-cell imaging, genomic approaches, and mathematical modeling, we find that hESCs commit to exiting pluripotency unexpectedly early. We show that bone morphogenetic protein 4 (BMP4), an important differentiation trigger, induces a subset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
51
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 59 publications
6
51
2
Order By: Relevance
“…In this study, the expression levels of BMPs in TSPC was increased with aging and upon osteogenic induction, indicating the intimate relationship between BMP expression and osteogenic differentiation potential of TSPC. In addition, BMP-2 could increase the osteogenic differentiation potential of TSPCs in this study, and BMPs also regulated differentiation ability of other cell species, such as tenocytes (Sato et al, 1988), embryonic stem cells (Gunne-Braden et al, 2020), and MSCs (Zhang et al, 2019). At the same time, we have tested the effect of noggin on the osteogenic differentiation of TSPCs in vitro, and the results showed that the addition of noggin could inhibit BMP-induced enhancement of osteogenic differentiation of TSPCs.…”
Section: Discussionmentioning
confidence: 60%
“…In this study, the expression levels of BMPs in TSPC was increased with aging and upon osteogenic induction, indicating the intimate relationship between BMP expression and osteogenic differentiation potential of TSPC. In addition, BMP-2 could increase the osteogenic differentiation potential of TSPCs in this study, and BMPs also regulated differentiation ability of other cell species, such as tenocytes (Sato et al, 1988), embryonic stem cells (Gunne-Braden et al, 2020), and MSCs (Zhang et al, 2019). At the same time, we have tested the effect of noggin on the osteogenic differentiation of TSPCs in vitro, and the results showed that the addition of noggin could inhibit BMP-induced enhancement of osteogenic differentiation of TSPCs.…”
Section: Discussionmentioning
confidence: 60%
“…This, combined with our study, suggests that one will likely find global community effects among ex vivo embryonic structures, in which large numbers of multicellular structures (e.g., blastocysts) communicate amongst them on a plate. Using our type of systematic approach, one may uncover such global community effects which may involve both secreted molecules (3,(57)(58)(59)(60)(61)(62) and cellcell contact-mediated communication (63)(64)(65)(66). The latter did not enter our analysis as we sparsely seeded near-single cells.…”
Section: Discussionmentioning
confidence: 99%
“…Dual SMAD signaling (BMP4 and TGF-β) activation leads to PS formation in ESCs while blocking ectodermal commitment. BMP4 in the presence of FGF2 is the critical regulator that leads to the upregulation of mesoderm-related genes ( Brachyury, Cdx2, Tbx3, and Gata4 ) in hESCs ( Gunne-Braden et al., 2020 ), whereas TGF-β inhibition accelerates mesoderm formation from PS and blocks endoderm specification ( Loh et al., 2014 ). This strategy was used to differentiate ESCs into hematopoietic precursor ( Pearson et al., 2008 ; Zhang et al., 2008 ) and endothelial progenitors ( Goldman et al., 2009 ) that was instrumental in the formation of cardiac organoids resembling human fetal hearts ( Voges et al., 2017 ).…”
Section: Mimicking Development To Generate Multi-lineage Organoidsmentioning
confidence: 99%